Lifetime Attributable Risk for Breast Cancer Induced by High-Resolution Computed Tomography During COVID-19 Pandemic - Roya Sahebi; Jafar Hassanzadeh; Rezvan Ravanfar Haghighi; Mehrzad Lotfi; Alireza Mirahmadizadeh (Journal of Family and Reproductive Health)
Objective: The widespread utilization of high-resolution computed tomography (HRCT) for diagnosing and management of COVID-19 during the pandemic has prompted worries regarding a potential rise in future breast cancer cases. We aimed to estimate the Life Attributable Risk (LAR) of breast cancer in Shiraz, Iran, linked to HRCT use during the COVID-19 pandemic. Materials and methods: A cross-sectional study was conducted at Namazi Hospital in Shiraz from February 2, 2020, to December 31, 2022.The Imaging Performance Assessment of CT Scanners (ImPACT) patient dosimetry calculator was used to determine organ doses. LAR was computed utilizing the Biological Effects of Ionizing Radiation (BEIR) Committee models. Results: The sample size was 666, with ages spanning from 15 to 95 years. 25% (168) had HRCT more than once (2 to 8 times). The mean and 95% uncertainty limits (UL) for Total LAR of breast cancer, considering both single and multiple doses of radiation exposure, was 217 (95% UL, 194-244) per 100,000 persons. Conclusion: According to our research, the risk of potential breast cancer should not be overlooked. It is advised to use the ultra-low-dose protocol over the low-dose in HRCT. Physicians, pulmonologists, and infectious disease specialists are advised to avoid unnecessary and repeated requests for chest HRCT in a short period.